Correlates of innovative behavior in school administration - Santos, Consorcia Galang Avenir 1920-
This study aimed to identify the intrinsic or personal variables inherent in the school administrator as an individual, and the extrinsic school variables in which the principal operates where he has little or no control. It also analyzed differences between the innovating and non-innovating groups of school administrators and explored cognitive, affective, and psychomotor characteristics or conditions which enhance or impede implementationof instructional innovations. This study was conducted in the Division of City Schools, Manila, where the respondents were chosen through random sampling in both elementary and secondary levels. Questionnaires and interviews were conducted to gather data from the school administrators. Of the twenty independent variables tested, 11 which were mostly personal variables, were found to be related to innovative behavior. There is also a consistency among perceptions of assisting principals and supervisors on the principals. The most and least innovating principals truly differed as was shown by the major instructional innovations implemented in their school.